Factors Related to Healing Process of Sectio Caesarea Surgical Wound (Unnes Journal of Public Health, 2018)
ABSTRACT Sectio caesarea surgical wound is a disorder in the incontinence of cells due to surgery performed to remove the fetus and placenta by opening the abdominal wall for certain indications. The aim of the study was to analyze and make a modeling of the relationship of factors in healing the sectio caesarea surgical wounds. This research is an analytic observational study with cross-sectional design. The sample in this study were 42 mothers with post sectio caesarea surgery at Prof. DR. W.Z. Johannes Kupang Public Hospital. Sampling was performed by simple random sampling. Data analysis was carried out in a bivariate and multivariate analysis. The results of the bivariate analysis found that the variables that give risk to wound healing were age (p = 0.041; RP = 3.4), discharge planning (p = 0.004; RP = 4.75), personal hygiene (p = 0.003; RP = 0.18), nutritional status (p = 0.013; RP = 0.15). Multivariate analysis found three variables that consistently provide risks to wound healing, namely discharge planning (p = -2.078; RP = 829 95% CI), personal hygiene (p = -1.852; RP = 1.039 95% CI), nutritional status (p = -2,374; RP = 1,023 95% CI). Probability model for healing the surgical wound at Prof. Dr. W.Z. Johannes, namely personal hygiene, nutritional status, discharge planning are factors related to wound healing. Keywords : sectio caesarea, wound, discharge planning, personal hygiene ABSTRAK Luka operasi sectio caesarea adalah gangguan dalam inkontuinitas sel akibat dari pembedahan yang dilakukan untuk mengeluarkan janin dan placenta dengan membuka dinding perut atas indikasi tertentu. Tujuan penelitian untuk menganalisis dan membuat pemodelan hubungan faktor pada penyembuhan luka operasi sectio caesarea. Penelitian ini merupakan studi observasional analitik dengan desain cross sectional. Sampel pada penelitian ini sebanyak 42 ibu post operasi sectio caesarea di RSUD Prof. DR. W.Z. Johannes Kupang. Pengambilan sampel secara simple random sampling. Analisis data dilakukan secara bivariat dan multivariat. Hasil analisis bivariat menemukan variabel yang memberikan risiko terhadap penyembuhan luka adalah umur (p=0,041; RP=3,4), discharge planning (p=0,004; RP=4,75), personal hygiene (p=0,003; RP=0,18), status gizi (p=0,013; RP=0,15). Analisis multivariat menemukan tiga variabel yang konsisten memberikan risiko terhadap penyembuhan luka yaitu discharge planning (p= -2.078; RP=829 95% CI), personal hygiene (p= -1.852; RP= 1,039 95% CI), status gizi (p= -2.374; RP=1,023 95% CI). Model probabilitas penyembuhan luka operasi di RSUD Prof. Dr. W.Z. Johannes yaitu personal hygiene, status gizi, discharge planning merupakan faktor yang berhubungan dengan penyembuhan luka. Kata kunci : sectio caesarea, luka, discharge planning, personal hygiene